2022
DOI: 10.3390/ijms231810349
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of Piromelatine Treatment on Sleep-Wake Cycle and Sleep Structure of Prenatally Stressed Rats

Abstract: Prenatal stress (PNS) impairs the circadian rhythm of the sleep/wake cycle. The melatonin (MT) analogue Piromelatine (Pir) was designed for the treatment of insomnia. The present study aimed to explore effects of Pir on circadian rhythmicity, motor activity, and sleep structure in male and female rats with a history of prenatal stress (PNS). In addition, we elucidated the role of MT receptors and brain-derived neurotrophic factor (BDNF) to ascertain the underlying mechanism of the drug. Pregnant rats were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…The drug was chronically injected intraperitoneally at a dose of 20 mg/kg (i.p.) that did not affect locomotor activity [ 15 ], thereby eliminating possible false positive responses. Our results agreed with the report of He et al (2013) [ 31 ], who demonstrated that a single administration of Piromelatine at a dose of 50 mg/kg either in the morning or in the afternoon did not change both the short- and long-term memory in an ORT test of male Sprague–Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The drug was chronically injected intraperitoneally at a dose of 20 mg/kg (i.p.) that did not affect locomotor activity [ 15 ], thereby eliminating possible false positive responses. Our results agreed with the report of He et al (2013) [ 31 ], who demonstrated that a single administration of Piromelatine at a dose of 50 mg/kg either in the morning or in the afternoon did not change both the short- and long-term memory in an ORT test of male Sprague–Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is involved in neuronal plasticity, hippocampal synaptogenesis and spatial memory formation [ 12 , 13 , 14 ]. Deterioration of BDNF is associated with depression, disturbed circadian rhythms and cognitive deficits [ 1 , 13 , 15 ]. This essential for brain plasticity molecules, via binding to the receptor tyrosine kinase B (TrkB), activate several signaling pathways such as the Ras-mitogen-activated protein kinase (MAPK), the phosphatidylinositol-3-kinase (PI3K) and the phospholipase Cγ (PLC-γ) pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations